The Economics Analysis, the National Economic Mentality and the Economic thought of Lithuania - Martišius, Stanislovas Algimantas (Ekonomika, 2005)
The publication discusses the alteration of economics thoughts at the end of 20th century. An author seeks is to activate methodological theoretical investigations of economic though there in Lithuania. In the article, the theoretical concepts prevailing in Lithuania are analyzed against the background of the development of the worlds economic thought. The publication suggests to establish faculties of social sciences in the main Lithuanian universities and economic profile science institutions of university stature. In authors view, this would set the Lithuanian economics and studies to the European standards.